Indigenising positive psychology in the ‘Handbook of Quality of Life in African Societies’ - Jan Alewyn Nel (Journal de Ciencias Sociales, 2021)
This book review highlights the main themes of the Handbook of Quality of Life in African Societies (as edited by Prof Irma Eloff from the University of Pretoria), focusing on meaning and language, culture (and positive culture), and social responsibility. The interrelatedness of all five parts of the book (from a macro, meso and micro perspective) are discussed with specific mention of Ubuntu and its relevance in investigating the phenomenon of quality-of-life. The review emphasises the need for exploratory and indigenous research in communities where social association is of immense importance and to contextualise quality-of-life from this perspective. This book is recommended for scholars who wishes to utilise indigenous methodologies and to deeper understand the diverse influences and social impact on the quality-of-life of individuals south of the Sub-Saharan Africa.